PERAN HUKUM DALAM MENYELESAIKAN SENGKETA TANAH ADAT DI KAMPUNG KABARE DISTRIK WAIGEO UTARA KABUPATEN RAJA AMPAT - Lapon, Habel Ananias; Syauta, Novalin M.; Baho, Dayen (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The purpose of writing this final assignment is to determine the factors that cause customary land disputes in Kabare Village and to determine the role of law in resolving customary land disputes in Kabare Village, North Waigeo District, Southwest Papua Province. The research method used is empirical normative research type, the type and source of data used is primary and secondary data, data collection techniques are through literature study, interviews, observation and documentation and the data analysis technique used is descriptive qualitative. The research results are the factors that cause customary land disputes in Kabare Village, North Waigeo District, namely, land boundaries, renting and buying and selling land and law does play a very important role in resolving disputes but its implementation is not yet optimal, especially for law. national, while customary law itself sometimes lacks awareness and compliance from the community in Kabare Village, North Waigeo District, Raja Ampat Regency.Keywords: Role of Law, Disputes, Customary Land